Decision support based on genomics: integration of data- and knowledge-driven reasoning. (14th April 2010) - Sfakianakis, S.; Blazantonakis, M.; Dimou, I.; Zervakis, M.; Tsiknakis, M.; Potamias, G.; Kafetzopoulos, D.; Lowe, D.
The breadth and depth of available clinico-genomic information, present an enormous opportunity for improving our ability to study disease mechanisms and meet the individualised medicine needs. A difficulty occurs when the results are to be transferred 'from bench to bedside'. Diversity of methods is one of the causes, but the most critical one relates to our inability to share and jointly exploit data and tools. This paper presents a perspective on current state-of-the-art in the analysis of clinico-genomic data and its relevance to medical decision support. It is an attempt to investigate the issues related to data and knowledge integration.